Attenuation of Splanchnic Autotransfusion Following Noninvasive Ultrasound Renal Denervation: A Novel Marker of Procedural Success - Saxena, Manish; Shour, Tariq; Shah, Mussadiq; Wolff, Christopher B.; Julu, Peter O.O.; Kapil, Vikas; Collier, David J.; Ng, Fu Liang; Gupta, Ajay; Balawon, Armida; Pheby, Jane; Zak, Anne; et al. (Journal of the American Heart Association, 2018)
BACKGROUND: Renal denervation has no validated marker of procedural success. We hypothesized that successful renal denervation would reduce renal sympathetic nerve signaling demonstrated by attenuation of α-1-adrenoceptor-mediated autotransfusion during the Valsalva maneuver. METHODS AND RESULTS: In this substudy of the Wave IV Study: Phase II Randomized Sham Controlled Study of Renal Denervation for Subjects With Uncontrolled Hypertension, we enrolled 23 subjects with resistant hypertension. They were randomized either to bilateral renal denervation using therapeutic levels of ultrasound energy (n=12) or sham application of diagnostic ultrasound (n=11). Within-group changes in autonomic parameters, office and ambulatory blood pressure were compared between baseline and 6 months in a double-blind manner. There was significant office blood pressure reduction in both treatment (16.1±27.3 mm Hg, P<0.05) and sham groups (27.9±15.0 mm Hg, P<0.01) because of which the study was discontinued prematurely. However, during the late phase II (Iii) of Valsalva maneuver, renal denervation resulted in substantial and significant reduction in mean arterial pressure (21.8±25.2 mm Hg, P<0.05) with no significant changes in the sham group. Moreover, there were significant reductions in heart rate in the actively treated group at rest (6.0±11.5 beats per minute, P<0.05) and during postural changes (supine 7.2±8.4 beats per minute, P<0.05, sit up 12.7±16.7 beats per minute, P<0.05), which were not observed in the sham group. CONCLUSIONS: Blood pressure reduction per se is not necessarily a marker of successful renal nerve ablation. Reduction in splanchnic autotransfusion following renal denervation has not been previously demonstrated and denotes attenuation of (renal) sympathetic efferent activity and could serve as a marker of procedural success. CLINICAL TRIAL REGISTRATION: URL: https://www.clinicaltrials.gov. Unique identifier: NCT02029885.
EVALuna2:34506